2005
DOI: 10.1103/physrevb.71.174201
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Raman effects and internal stress in network glasses

Abstract: Raman scattering from binary Ge x Se 1−x glasses under hydrostatic pressure shows onset of a steady increase in the frequency of modes of corner-sharing GeSe 4 tetrahedral units when the external pressure P exceeds a threshold value P c . The threshold pressure P c ͑x͒ decreases with x in the 0.15Ͻ x Ͻ 0.20 range, nearly vanishes in the 0.20Ͻ x Ͻ 0.25 range, and then increases in the 0.25Ͻ x Ͻ 1 / 3 range. These P c ͑x͒ trends closely track those in the nonreversing enthalpy, ⌬H nr ͑x͒, near glass transitions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
193
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(214 citation statements)
references
References 35 publications
21
193
0
Order By: Relevance
“…Boolchand et. al. suggested that chalcogenide glasses display three elastic phases as a function of their mean coordination number: floppy phase, Intermediate phase (IP) and stressed rigid phase (Fig 2) [ [10][11][12][13][14][15][16][17][18][19][20][21][22]. Glass compositions in floppy phase and stressed rigid phase are usually poor glass formers due to the high internal stress in their molecular structure.…”
Section: Chalcogenide Materialsmentioning
confidence: 99%
“…Boolchand et. al. suggested that chalcogenide glasses display three elastic phases as a function of their mean coordination number: floppy phase, Intermediate phase (IP) and stressed rigid phase (Fig 2) [ [10][11][12][13][14][15][16][17][18][19][20][21][22]. Glass compositions in floppy phase and stressed rigid phase are usually poor glass formers due to the high internal stress in their molecular structure.…”
Section: Chalcogenide Materialsmentioning
confidence: 99%
“…The idea has more than one source: quite early, one of us suggested that some network glasses could be self-organized and that this organization would optimize their ability to fill space with a constrained and compacted (''folded''), yet unstressed (easily deformed), network (3). The relevance of these ideas to proteins became much greater after the discovery of the stressfree reversibility window in the phase diagrams of both chalcogenide and oxide network glasses as well as solid electrolytes (4,5); this discovery solves the otherwise intractable problem of entanglement of exponentially complex, deformed networks, which overhung all such networks (network glasses as much as proteins).…”
mentioning
confidence: 99%
“…It also involves compacting the protein in a stress-free way similar to that found in network glasses in the reversibility window (3)(4)(5). Hydro(philic,phobic) residues will have large (small) SASA, which will generally change gradually, if that is allowed by connectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The internal networks associated with this novel phase have properties of great technological importance: They are rigid but still free of internal stress. 3 That combination of properties makes it possible to produce window glass on large scales without having it crack or crystallize.…”
mentioning
confidence: 99%